Zhao Yizhen and the Thunder Method Inherited from His Master Zhang Tianquan - Xu, Wei (Religions, 2023)
Zhao Yizhen (?–1382) was one of the most important figures in the history of Daoism in the Yuan and Ming Dynasties. His master, Zhang Tianquan (1275–?), was recorded to be a disciple of Jin Pengtou (?–1341), a famous master of inner alchemy in the late Yuan, in the poems written by Zhao Yizhen himself and in the biography of Zhao Yizhen written by Zhang Yuchu (1359–1410), the 43rd Heavenly Master. According to these records, we know that the Method that Zhao Yizhen learned from Zhang Tianquan was only about inner alchemy, inherited from Jin Pengtou. But this story does not include all the facts. Since we have found the biography of Zhang Tianquan, which is preserved in rare editions of Lishi Zhenxian Tidao Tongjian collected in the libraries of Beijing and Taipei, we can determine that what Zhang Tianquan was aware of and famous for was indeed the Thunder Method of Hunyuan. With the evidence found in Daofa Huiyuan, we can conclude that Zhao Yizhen was also very familiar with the Thunder Method of Hunyuan, which must have been inherited from Zhang Tianquan, and he tried to merge it into his own ritual system of the Qingwei tradition.